On the anarchy of poetry and philosophy : a guide for the unruly - Bruns, Gerald L. (Perspectives in continental philosophy., 2006)
This book takes seriously the transformation of art into philosophy, focusing upon the systematic interest that so many European philosophers take in modernism. Among the philosophers Gerald Bruns discusses are Theodor W. Adorno, Maurice Blanchot, Arthur Danto, Stanley Cavell, Hans-Georg Gadamer, Michel Foucault, Gilles Deleuze and Felix Guattari, Jacques Derrida, Jean-François Lyotard, Jean-Luc Nancy, Philippe Lacoue-Labarthe, and Emmanuel Levinas. As Bruns demonstrates, the difficulty of much modern and contemporary poetry can be summarized in the idea that a poem is made of words, not of any of the things that we use words to produce: meanings, concepts, propositions, narratives, or expressions of feeling. Many modernist poets have argued that in poetry language is no longer a form of mediation but a reality to be explored and experienced in its own right.